The Development of E-Pocket Book HSK 3 Learning Media for Students. Class XI IBB SMA Nurul Jadid Paiton Probolinggo - Siti Aisyah; Octi Rjeky Mardasari; Herri Akhmad Bukhori (Universitas Negeri Malang, 2025)
The purpose of this research is to design E-Pocket Book HSK 3 learning media for grade XI students of Language and Culture Program (IBB) at Nurul Jadid Paiton Probolinggo Senior High School. This learning media was developed to facilitate the learning process of Chinese, especially to prepare students for the HSK 3 examination, which is abbreviated from (Hanyu Shuiping Kaoshi). The development process used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which consists of five main stages. This research uses qualitative data as the type of data collected, which is collected through closed and open questionnaire sheets as data collection instruments. The E-Pocket Book HSK 3 media has obtained validation from media experts and material experts, and has been tested on twenty-one XI IBB class students and Chinese language teachers at Nurul Jadid Paiton Probolinggo Senior High School. According to the results obtained, it can be concluded that the HSK 3 E-Pocket Book is effective in increasing students' learning motivation and making it easier for them to prepare for the HSK 3 exam. In addition, this media also facilitates students to access materials independently